2011
DOI: 10.1186/2110-5820-1-13
|View full text |Cite
|
Sign up to set email alerts
|

Understanding urine output in critically ill patients

Abstract: Urine output often is used as a marker of acute kidney injury but also to guide fluid resuscitation in critically ill patients. Although decrease of urine output may be associated to a decrease of glomerular filtration rate due to decrease of renal blood flow or renal perfusion pressure, neurohormonal factors and functional changes may influence diuresis and natriuresis in critically ill patients. The purpose of this review is to discuss the mechanisms of diuresis regulation, which may help to interpret the ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(71 citation statements)
references
References 68 publications
4
66
1
Order By: Relevance
“…The primary outcome measure was AKI as defined by the AKI Network based on changes in serum creatinine concentrations [27] Urine output was not used to identify AKI in this study to exclude the effect of diuretic administration [28]. The serum creatinine measured on the third postoperative day, compared with the most recent preoperative measurement, was used to identify AKI to minimize the dilutional effects in relation to cardiopulmonary bypass [29].…”
Section: Methodsmentioning
confidence: 99%
“…The primary outcome measure was AKI as defined by the AKI Network based on changes in serum creatinine concentrations [27] Urine output was not used to identify AKI in this study to exclude the effect of diuretic administration [28]. The serum creatinine measured on the third postoperative day, compared with the most recent preoperative measurement, was used to identify AKI to minimize the dilutional effects in relation to cardiopulmonary bypass [29].…”
Section: Methodsmentioning
confidence: 99%
“…In the absence of severe volume depletion or volume overload, however, physical examination results and clinical judgment have not been shown to be reliable predictors of volume status, [19][20][21][22][23][24][25] nor have specific objective measures that frequently help inform clinical judgment, such as systolic blood pressure, 26,27 shock index, 28 and urine output. 29,30 In sum, neither of the approaches to fluid resuscitation used in the ARISE trial-CVP and clinical judgment-has been shown to reliably predict volume status. A study comparing the utility of 2 variables that are unable to accurately predict the outcome in question would not be expected to result in meaningful intergroup differences.…”
Section: Answermentioning
confidence: 99%
“…An increase in intraabdominal pressure during laparoscopic surgery, mechanical ventilation with positive end-expiratory pressure, and pain and surgical stress with release of an antidiuretic hormone are all factors inducing antidiuresis. 25 even a minor surgical injury can impair renal fluid elimination after fluid loading. 26 In a randomized controlled trial, urine output and postoperative creatinine serum concentration were not affected in obese patients undergoing laparoscopic surgery, who were randomly assigned to intraoperatively receive high (10 ml·kg −1 ·h −1 ; n = 55) or low (4 ml·kg −1 ·h −1 ; n = 52) volumes of Ringer's lactate.…”
Section: How Should Fluid Administration With Urine Output Be Guided mentioning
confidence: 99%